Use of talc as low-cost clarifier for wastewater - Grafia, Ana Luisa (2014)
Talc is proposed as a low-cost mineral for wastewater clarification. In this sense, adsorption of methylene blue (MB) from aqueous solutions was studied comparatively by using sepiolite (qualified as very good adsorbent) and two talc samples with different particle size and purity degree. The MB adsorption was assessed by determining remnant dye in the supernatant using UV-vis spectroscopy and by detecting dye adsorbed on mineral samples through thermogravimetric analysis and infrared spectroscopy. Both isothermal curves and kinetic studies demonstrate that talc is a good dye adsorbent. Particularly, with dye concentrations similar to those of textile wastewater, talc was demonstrated to adsorb the same dye content of sepiolite at similar times. Natural talc could be employed as a low-cost alternative in wastewater treatment for the removal of cationic dyes.